Snapshot in surgery: intraperitoneal encapsulated fat necrosis. Issue 2 (4th December 2014) - Oh, Han Boon; Arab, Nahlah; Teo, Lynette; Lieske, Bettina
<x xml:space="preserve">Abstract</x> A 66‐year‐old man with rectal cancer was found to have an incidental ring‐like lesion in the left rectovesical pouch. Histology revealed an encapsulated fat necrosis. Intraperitoneal encapsulated fat necroses are postulated to be a result of infarcted epiploic appendages resulting in a free‐floating lesion. <boxed-text content-type="graphic" id="ccr3173-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>